Grain yield, cooking quality, and aroma of fragrant rice as affected by nitrogen source and method of application - Rajesh Chakraborty; Tuhin Suvra Roy; Jun-Ichi Sakagami (AIMS Agriculture and Food)
One constraint is the incapacity of existing agronomic studies on rice yield, aroma, and cooking quality to fully assess the effects of various applications and sources of nitrogen (N) fertilizer. It is challenging for us to understand how different N inputs impact rice's sensory and cooking qualities in addition to crop productivity because of this research gap. So, a two-year pot experiment was conducted at Sher-e-Bangla Agricultural University, Dhaka, under an open field plastic net house from July 15 to December 4 in 2020 and 2021. The study used Bangladesh Rice Research Institute (BRRI) dhan70 as the test crop. The experiment examined two factors: the methods and source of N application. Three methods of N application were tested: 100% soil application (NM1), 2% foliar spray at tillering and booting stages (NM2), and a combination of 50% soil application and 2% foliar spray at the booting stage (NM3). Three sources of N were also evaluated: Urea (NS1), ammonium nitrate (NS2), and ammonium sulfate (NS3). Total 41.0 kg N ha−1 was applied considering the nitrogen content in Urea (46%), ammonium nitrate (35%), and ammonium sulfate (21%). The experiment followed a randomized complete block design (RCBD) with three replications. The results indicated that the application of N significantly influenced most of the studied parameters. The combined application of N as a foliar dose and soil application, along with ammonium nitrate and ammonium sulfate, showed improved results for various parameters such as gelatinization temperature, gel consistency, protein content, cooking time, imbibition ratio, 2-AP content, grain aroma, and taste of BRRI dhan70 compared to 100% soil application of N. The highest grain yield and 2-AP was observed in the NM3NS3 treatment (35.437 g·pot−1 and 0.137 µg·g−1, respectively) which was statistical similar with NM3NS2 treatment while the lowest yield and 2-AP was recorded in NM1NS1 (24.877 g·pot−1 and 0.076 µg·g−1, respectively).